Havox: Um serviço para orquestração de tráfego em alto nível em redes OpenFlow - Silva, Rodrigo Soares e; Lucena, Sidney Cunha de (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS), 2018)
Software-defined networking has been providing more control to network operators, but generating several OpenFlow rules simultaneously is yet a tough job. There are already research projects that generate a set of rules for basic network operations, as well as tools with their own grammars which parse high level network policy descriptions and translate them to rules. It was observed that a combination of these solutions can generate a new resource capable of giving to network administrators a friendly configuration language to help them define how data traffic should be forwarded. This work presents Havox, a service meant to help with traffic orchestration through a simple, high level configuration language based on OpenFlow fields. Experiments show a considerable reduction of network programming effort in a scalable way, reducing both the number of parameters and the number of lines of code.